2021
DOI: 10.3389/fphar.2021.778041
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Herbal Extracts of Traditional Chinese Medicine Applied with the Biomaterials: For the Current Applications and Advances in the Musculoskeletal System

Abstract: Traditional Chinese medicine (TCM) has demonstrated superior therapeutic effect for musculoskeletal diseases for thousands of years. Recently, the herbal extracts of TCM have received rapid advances in musculoskeletal tissue engineering (MTE). A literature review collecting both English and Chinese references on bioactive herbal extracts of TCM in biomaterial-based approaches was performed. This review provides an up-to-date overview of application of TCMs in the field of MTE, involving regulation of multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 132 publications
(127 reference statements)
0
6
0
Order By: Relevance
“…Jia et al (2015) [ 63 ] prepared ICA molecularly imprinted polymers by precipitation polymerization using acrylamide as functional monomer, ethylene glycol dimethacrylate as cross-linker, and methanol:acetonitrile mixture (3:1, v / v ) as the reaction solvent, in a molar ratio of template molecule:functional monomer:cross-linker of 1:6:80. An innovative therapy using autologous conditioned serum was proposed as being able to improve tissue regeneration and to reduce the degenerative mechanisms of OA [ 23 , 53 ]. Moreover, ICA-conditioned serum and ICA-conditioned serum combined with chitosan had a positive effect on primary rabbit chondrocyte proliferation and it was also demonstrated the regeneration of cartilage in rabbit osteochondral defect models [ 53 ].…”
Section: Hydrogels and Scaffolds Enriched With Ica For Osteochondral ...mentioning
confidence: 99%
See 3 more Smart Citations
“…Jia et al (2015) [ 63 ] prepared ICA molecularly imprinted polymers by precipitation polymerization using acrylamide as functional monomer, ethylene glycol dimethacrylate as cross-linker, and methanol:acetonitrile mixture (3:1, v / v ) as the reaction solvent, in a molar ratio of template molecule:functional monomer:cross-linker of 1:6:80. An innovative therapy using autologous conditioned serum was proposed as being able to improve tissue regeneration and to reduce the degenerative mechanisms of OA [ 23 , 53 ]. Moreover, ICA-conditioned serum and ICA-conditioned serum combined with chitosan had a positive effect on primary rabbit chondrocyte proliferation and it was also demonstrated the regeneration of cartilage in rabbit osteochondral defect models [ 53 ].…”
Section: Hydrogels and Scaffolds Enriched With Ica For Osteochondral ...mentioning
confidence: 99%
“…Moreover, ICA-conditioned serum and ICA-conditioned serum combined with chitosan had a positive effect on primary rabbit chondrocyte proliferation and it was also demonstrated the regeneration of cartilage in rabbit osteochondral defect models [ 53 ]. Moreover, it was observed that the ICA-conditioned serum and hyaluronic acid treatment of rabbit femoral condyle have regenerated the cartilage and subchondral bone [ 23 ]. In vitro and in vivo studies have investigated the potential of several cytocompatible, biomimetic biomaterials containing ICA and natural polymers (fibrin, silk fibrin, hyaluronan, alginate, chitosan, COL), synthetic polymers (polylactic acid, poly(lactic-co-glycolic acid), polyhydroxyethylmethacrylate, polycaprolactone), ceramics (hydroxyapatite, tricalcium phosphate), conditioned as composite hydrogels and scaffolds for cartilage repair and bone regeneration in osteochondral defects [ 82 ].…”
Section: Hydrogels and Scaffolds Enriched With Ica For Osteochondral ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Current research reveals that herbal extracts represent a promising avenue for treating systemic diseases ( Zhang et al, 2019a ; Jabbari et al, 2020 ; Tang, Hosein & Mattioli-Belmonte, 2021 ; Pandey & Nimisha, 2020 ). Traditional medicine (TCM) has demonstrated superior efficacy in addressing locomotor system-related diseases and autoimmune disorders in recent years ( Jabbari et al, 2020 ; Pandey & Nimisha, 2020 ; Zhou et al, 2010 ; Li et al, 2021 ; Chen et al, 2022a ). Tripterygium wilfordii Hook F is renowned for its dehumidiferous roots, which produce Tripterygium glycosides (TGTs).…”
Section: Introductionmentioning
confidence: 99%